Early Detection of Cognitive, Language, and Motor Delays for Low-Income Preterm Infants: A Brazilian Cohort Longitudinal Study on Infant Neurodevelopment and Maternal Practice - Valentini, Nadia C.; de Borba, Luana S.; Panceri, Carolina; Smith, Beth A.; Procianoy, Renato S.; Silveira, Rita C. (Frontiers in Psychology, 2021)
Aim: This study examined the neurodevelopment trajectories, the prevalence of delays, and the risks and protective factors (adverse outcomes, environment, and maternal factors) associated with cognitive, motor, and language development for preterm infants from 4- to 24-months. Method: We assessed 186 preterm infants (24.7% extremely preterm; 54,8% very preterm; 20,4% moderate/late preterm) from 4- to 24-months using the Bayley Scales of Infant Development - III. Maternal practices and knowledge were assessed using the Daily Activities of Infant Scale and the Knowledge of Infant Development Inventory. Birth risks and adverse outcomes were obtained from infant medical profiles. Results: A high prevalence of delays was found; red flags for delays at 24-months were detected at 4- and 8-months of age. The neurodevelopmental trajectories showed steady scores across time for cognitive composite scores for extremely- and very-preterm infants and for language composite scores for the extremely- and moderate/late-preterm; a similar trend was observed for the motor trajectories of moderate/late preterm. Changes over time were restricted to motor composite scores for extremely- and very-preterm infants and for cognitive composite scores for moderate/late preterm; declines, stabilization, and improvements were observed longitudinally. Positive, strong, and significant correlations were for the neurodevelopment scores at the first year of life and later neurodevelopment at 18 and 24 months. The cognitive, language, and motor composite scores of extremely and very preterm groups were associated with more risk factors (adverse outcomes, environment, and maternal factors). However, for moderate/late preterm infants, only APGAR and maternal practices significantly explained the variance in neurodevelopment. Discussion: Although adverse outcomes were strongly associated with infant neurodevelopment, the environment and the parents’ engagement in play and breastfeeding were protective factors for most preterm infants. Intervention strategies for preterm infants should start at 4- to 8-months of age to prevent unwanted outcomes later in life.